Forming of CdZnTe thin films grown by hot wall epitaxy and their properties - Vuichyk, M.; Rashkovets’kyi, L.; Lavoryk, S.; Lytvyn, P.; Svezhentsova, K. (Physics and Chemistry of Solid State, 2021)
In this work morphological, X-ray structural and optical studies of CdZnTe films grown by hot wall epitaxy method at relatively low substrate temperatures were performed. Possible mechanisms and processes of self-organization that occur during the growth of such structures are considered. It is shown that at thickness of film more than 130 nm on the surface, large (lateral size 150 - 200 nm, height - up to 10 nm) and small crystals are observed. The thicknesses and energy of the band gap width of the CdZnTe films grown at different growth times were determined. It is shown that the film absorption edge in the transmission spectra depends on the film thickness and the reasons for the shift of the film absorption edge are discussed.